(3ZGjI GdSQhQ TQM OjhGf GdTPhQs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3GHf GQaY QGSg GdCfOdSj GdLjGfj, GHf GQaY QGSg GdCfOdSj GdLjGfj,J (B593 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdMceI GdTQjaI cfR Gddg JYGdi dcd hGQO HYdhe ai GdbSeI GdSGHbI s
(3BNQgG (B:s
(3hbO bQHfGg ddage hdNUfGg ai bOQ GdSOS ef CUdg hGdMeO ddg QH GdYGdejf Ydi MSf GdeHOC hJeGe GdNJGe s
(3eQJH Ydi CQHYI CLRGAs
(3cJHJ ai fUa TYHGf SfI (B1091s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdcjejGA h GdWHjYjGJs